APPLICATION OF SMARTPHONE BASED QUIZIZZ APPLICATIONS AS A LEARNING MEDIA IN THE ENVIRONMENT OF UNIVERSITAS PGRI MADIUN - Wibawa, Ramadhan Prasetya (Fakultas Ekonomi, Universitas Negeri Semarang, 2019)
This research stems from the learning that is applied to the accounting and economic education environment of PGRI Madiun University which tends to be still content transmission and teacher centered. These learning activities resulted in students being limited in developing creativity, understanding the concepts, and students still using their cellphones for learning while in class so that student learning outcomes are still not optimal. The main objective of this research is to apply smartphone-based quizizz applications as learning media in the PGRI Madiun University environment. The method used in this research is descriptive-qualitative. This research was conducted at the University of PGRI Madiun. The subject of this study is a study program in accounting education and economic education. The results showed that in general students were positive about the application of smartphone-based quizizz applications as learning media. The application of smartphone-based quizizz applications as a learning media as a learning media has increased the effectiveness and efficiency of time in learning and improved information technology skills, discipline in completing lecture tasks, and facilitates communication with lecturers supporting the courses concerned